PENERAPAN KEDISIPLINAN DALAM MENGURANGI KEJENUHAN SISWA KELAS V (STUDI KASUS DI SDN 20 KAMPUNG LORONG) - Nerla Hismarlia; Purniadi Putra, Rona (ADISAM PUBLISHER, 2024)
This research aims to find out and obtain information about the form of boredom of class V students at the 20 Kampung Lorong State Elementary School, the application of discipline by teachers in class V at the 20 Kampung Lorong State Elementary School, and obstacles to the application of discipline in class V at the 20 Kampung State Elementary School. Hallway. This research uses a qualitative research approach with the type of research being a case study. The results of this study concluded that the forms of boredom of class V students at the 20 Kampung Lorong Elementary School were in the form of: chatting with other students without paying attention to the material being taught, making noise during the learning process, and parental factors such as lack of parental attention, apart from that, the implementation of discipline in class V at the 20 Kampung Lorong Elementary School, namely: disciplinary programs such as: extracurricular scouts, teachers making case books for students with problems, rules and regulations, holding school environment cleanliness activities and cooperative relationships with students' parents and as for obstacles to the application of discipline in class V at the 20 Kampung Lorong Elementary School, namely: internal factors such as lack of student interest and motivation, external factors such as family factors, namely lack of support from parents, school factors, namely students who often lie, and community factors, namely social friends and students who live in less conducive environments.